2016
DOI: 10.1038/srep21566
|View full text |Cite
|
Sign up to set email alerts
|

Chemical insights into the roles of nanowire cores on the growth and supercapacitor performances of Ni-Co-O/Ni(OH)2 core/shell electrodes

Abstract: Nanostructured core/shell electrodes have been experimentally demonstrated promising for high-performance electrochemical energy storage devices. However, chemical insights into the significant roles of nanowire cores on the growth of shells and their supercapacitor behaviors still remain as a research shortfall. In this work, by substituting 1/3 cobalt in the Co3O4 nanowire core with nickel, a 61% enhancement of the specific mass-loading of the Ni(OH)2 shell, a tremendous 93% increase of the volumetric capaci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 63 publications
1
5
0
Order By: Relevance
“…The CV trace in Figure a also indicated an additional minor peak at 1.36 V vs RHE (labeled as Peak III) during the forward scan and at 1.26 V vs RHE (labeled as Peak IV) during the reverse scan for La 1.4 Sr 0.6 Ni 0.9 Co 0.1 O 4+δ . The minor peak corresponds to the oxidation of Co 3+ /Co 4+ and was in accordance with previous findings in the literature. No corresponding peaks were evident for the oxidation of Mn 2+ or Fe 2+ . Interestingly, as the scan rate was elevated from 10 to 100 mV s –1 , an increase in the peak current density was observed, indicating the formation of a more substantial layer of −OOH species enriched with Ni 3+ on the catalyst’s surface (Figure S4).…”
Section: Resultssupporting
confidence: 91%
“…The CV trace in Figure a also indicated an additional minor peak at 1.36 V vs RHE (labeled as Peak III) during the forward scan and at 1.26 V vs RHE (labeled as Peak IV) during the reverse scan for La 1.4 Sr 0.6 Ni 0.9 Co 0.1 O 4+δ . The minor peak corresponds to the oxidation of Co 3+ /Co 4+ and was in accordance with previous findings in the literature. No corresponding peaks were evident for the oxidation of Mn 2+ or Fe 2+ . Interestingly, as the scan rate was elevated from 10 to 100 mV s –1 , an increase in the peak current density was observed, indicating the formation of a more substantial layer of −OOH species enriched with Ni 3+ on the catalyst’s surface (Figure S4).…”
Section: Resultssupporting
confidence: 91%
“…In contrast, the binary cobalt-nickel layered double hydroxides demonstrate superior electrochemical performance over single cobalt or nickel hydroxides by integrating the advantages of both components. Researchers have devoted considerable efforts to fabricate various Co-Ni hydroxide nanostructures to improve the electrochemical performance of Co-Ni hydroxides as high-performance electrode materials [22][23][24] . Sun and co-workers reported the morphology and structure evolution of the Ni-Co mixed hydroxides changing from nano-sheets, to nano-plates, nano-spheres, nano-rods and nano-particles through modulating the Co/Ni molar ratio in the initial reactant.…”
Section: Introductionmentioning
confidence: 99%
“…1,36 It is interesting to note that the electrode−electrolyte interface with fractal geometry offers an improved electrode−electrolyte interface. 1,9,36,37 Fractal objects have a higher surface area as compared to the substrates. 9,38,39 Many researchers have reported that the performance of a supercapacitor is enhanced with metal doping as well as the formation of nanocomposites.…”
Section: Introductionmentioning
confidence: 99%
“…9,38,39 Many researchers have reported that the performance of a supercapacitor is enhanced with metal doping as well as the formation of nanocomposites. [9][10][11]36,40,41 Recently, our group reported a high specific capacity (∼413 C g −1 ), energy density (∼45.95 Wh kg −1 ), and power density (∼2.6 kW kg −1 ) in an Sr(OH) 2 -based supercapacitive electrode. The natural abundance, low cost, electrochemical performance, and environment-friendly nature of this material has made it an efficient candidate that has attracted the researchers to use it as a new electrode for supercapacitors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation